Education for All – Message from Minister of Education 2019 - UMP, PNC (2019)
Minister of Education, Dr. Maszlee Malik presented his vision on the education sector for the year 2019 in his speech themed, ‘Education for All’ that emphasised on four aspects – quality, autonomy, collaboration and internalisation.